Codes for Compression and Error Detection - Pinto, Paulo (Cadernos do IME - Série Informática, 2022)
This article summarizes the main results about codes that combine the data compression power of Huffman trees with the error detection mechanisms proposed by Hamming. Two methods are described: the even trees method and the Hamming-Huffman trees method. Most of the works are the result of a close collaboration with Jayme Luiz Szwarcfiter.